Acceptance of QR code UiTM library among FSKM students / Amanina Abd Sukor - Abd Sukor, Amanina (2016)
Quick Response (QR) codes are two-dimensional patterned graphics that are readable by mobile devices to represent text and link to internet content. The implementation of QR code is not widely used in local libraries such as in universities and colleges. There are many ways of implementing QR code in library management systems such as information tracking, virtual library tour and promoting student engagement to the library. This study is done to identify the requirements needed for acceptance of implementing QR code in library management system. The case study for this research focuses on UiTM library management system, where the QR code is not fully implemented and well-functioning. The purpose of this study is to identify the acceptance factors of using QR code and to construct the acceptance model of QR code system to library management system. Furthermore, this study is adapted model from Technology Acceptance Model; where the factors suggested are 1) Perceived Convenience, 2) perceived Usefulness, 3) Perceived Ease of Use and 4) Perceived Interaction have significant influences in acceptance of QR code system. Moreover, this study applied quantitative approach where surveys are distributed to students in Faculty of Computer and Mathematical Sciences. The rationale for using students from this faculty is due to the participations and their ability and knowledge in understanding about QR code better. The results show the significant influenced by the acceptance of QR code system to the factor of Perceived Interaction. While factors of Perceived Convenience, Perceived Usefulness and Perceived Ease of Use are significantly influenced to the acceptance of QR code system. Based on these results, the acceptance model of QR code system to library management system is constructed and achieved which will benefits the UiTM library management in providing the model and requirements needed in implementing QR code system.